2022
DOI: 10.1249/mss.0000000000002921
|View full text |Cite
|
Sign up to set email alerts
|

Leg Dominance Does Not Influence Maximal Force, Force Steadiness, or Motor Unit Discharge Characteristics

Abstract: Purpose: The aim of our study was to compare maximal force, force steadiness, and discharge characteristics of motor units in tibialis anterior during contractions with the dorsiflexors of the dominant and nondominant legs at low-to-moderate target forces and three ankle angles. Methods: Twenty young adults performed maximal and submaximal isometric contractions (5%, 10%, 20%, 40%, and 60% of maximal voluntary contraction (MVC)) with the dorsiflexors of the dominant and nondominant legs at three ankle angles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Finally, our results revealed a slight but significant increase in peak force when the ankle was secured at a joint angle of 90° compared to 130° position (∼8.7%). This increase could be attributed, at least in part, to sarcomere overlengthening beyond the optimal overlap (Bigland‐Ritchie et al., 1992; Petrovic et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our results revealed a slight but significant increase in peak force when the ankle was secured at a joint angle of 90° compared to 130° position (∼8.7%). This increase could be attributed, at least in part, to sarcomere overlengthening beyond the optimal overlap (Bigland‐Ritchie et al., 1992; Petrovic et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study examined only the FDI muscle. A recent study analyzing MUs in the TA muscle reported that no asymmetry of MUs was observed in males (Petrovic et al 2022 ). Since the upper and lower extremities are used differently, it is likely that the motor control mechanisms are also different, but sex differences in other muscles need to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that when the ankle was secured at a joint angle of 90°, peak torque significantly increased compared to the 130° position (∼8.7%). The lower MVC values at 130° could be explained, at least in part, by sarcomere overlengthening beyond the optimal overlap (Bigland-Ritchie et al, 1992, Petrovic et al, 2022). Interestingly, in the current study there were no significant differences in torque steadiness between the 90° or 130° ankle joint positions.…”
Section: Discussionmentioning
confidence: 99%